ETIKA DAN PENAMPILAN PRAMUSAJI DI RESTORAN GRAND CENTRAL HOTEL PEKANBARU - Gustina Irmayanti Navili; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The etiquette and appearance of the waiter are an important part in improving the hotel's image. The ethical standards and appearance standards that must be applied by every restaurant waiter. This study aims to determine the ethical implementation and appearance of restaurant waiters at Grand Central Hotel Pekanbaru. This study uses a qualitative method with a descriptive approach. Data collection techniques used in the study were interviews, observation, and documentation. Informants involved in this study were Mr. Iwan as manager of the food & beverage service department at Grand Central Hotel Pekanbaru, Mrs. Indah as captain waiter the food & beverage service department at Grand Central Hotel Pekanbaru. Based on the results of the research on Ethics and Appearance of Restaurant Waiters at Grand Central Hotel Pekanbaru, it was considered quite good where every waiter had implemented ethical standards and appearance standards well. Of course, in the application of good ethics and appearance, there are waiters who have not applied these standards well, but this can be overcome by evaluating so that the ethics and appearance of the waiters at Grand Central Hotel Pekanbaru can be applied better. Keywords: Waitress, Ethics, Appearance, Service.